Development of Response Measurement Instruments Students on Learning - Karpin, Karpin; Juwaedah, Ade (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2019)
The research aims has measured student responses to learning process on what a significant impact on the lectures desire to implement various learning innovation. This article is intended to find out developing instruments for measuring student responses to learning based-on Hinkin’s model about instrument developing process. This research used quantitative approach in which data has collected 170 people as a sample, they are students of culinary study program at Indonesia University of Education. The instrument of this research used questionnaires contains three variables that are; the types of learning, the learning strategies, and the students responses of learning. This research found that the results of factor analysis on the indicators of the research variable are obtained; the factors from the learning type variable are constructive-interactive-passive-and active. The factors formed from the variable learning strategies are explanation and facilitation; and the factors formed by student responses to learning are value-positivity-distraction-and participation. The instrument that had been developed would be relevant for broader scope and context for learning other fields.